NILAI-NILAI KARAKTER KEKHUSUSAN HUBUNGAN DENGAN TUHAN DALAM NOVEL SEHIDUP SESURGA DENGANMU KARYA ASMA NADIA - Farma, Mahendra Adi; Bahardur, Iswadi; Samsiarni, Samsiarni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the character values of a special relationship with God depicted in the novel "Sehidup Sesurga Denganmu" by Asma Nadia. This novel was chosen because it presents a strong female main character, Dyah, who represents moral and spiritual values in everyday life. The method used in this study was descriptive qualitative with a content analysis approach. The data in this study consisted of quotations reflecting the attitudes, statements, and actions of Dyah that are relevant to the character's values. The results show that the value of a special relationship with God reflects the solemnity of Dyah's relationship with God. These values are not only demonstrated through the narrative but also through the conflicts and resolutions faced by the main character. This study concludes that literary works can be an effective tool in character education, particularly in shaping students' understanding of life values. By presenting an inspirational figure like Dyah, this novel is able to internalize moral messages in a touching and profound way. This research also contributes to the development of literature-based character literacy in educational settings.